Antena impressa com substrato de metamaterial desenvolvido com an?is met?licos fendidos circulares conc?ntricos - Jo?o Feliciano, Amilcar (2016)
This work deals with printed antennas developed on modified substrate through metallic printed rings on bottom face of radiator element. At first, it was developed a traditional printed antenna with politetrafluoretilene (PTFE) Diclad? 880 substrate, using a rectangular radiator and fed with microstrip line. Then, the substrate was modified by the insertion of split ring resonators, which resulted in a new antenna. Simulations and measurements were made for traditional as well as metamaterial antenna, with Matlab? and EMPro?. The results deal with theoretical evaluation, concerning to reflection coefficient improvement, antenna gain and frequency response.